2020
DOI: 10.1002/lno.11665
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns in greenhouse gas emissions from thermokarst lakes in Central Yakutia (Eastern Siberia)

Abstract: In the ice‐rich permafrost area of Central Yakutia (Eastern Siberia, Russia), climate warming and other natural and anthropogenic disturbances have caused permafrost degradation and soil subsidence, resulting in the formation of numerous thermokarst (thaw) lakes. These lakes are hotspots of greenhouse gas emissions, but with substantial spatial and temporal heterogeneity across the Arctic. We measured dissolved CO2 and CH4 concentrations in thermokarst lakes of Central Yakutia and their seasonal patterns over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…These values are among the highest CO 2 fluxes reported for tundra lakes (Table 1). However, higher CO 2 diffusive fluxes were reported from subarctic thermokarst lakes (> 350 mmol m −2 d −1 from yedoma landscape in Eastern Siberia, Hughes‐Allen et al (2020); 242 mmol m −2 d −1 from Quebec palsa peatlands, Matveev et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…These values are among the highest CO 2 fluxes reported for tundra lakes (Table 1). However, higher CO 2 diffusive fluxes were reported from subarctic thermokarst lakes (> 350 mmol m −2 d −1 from yedoma landscape in Eastern Siberia, Hughes‐Allen et al (2020); 242 mmol m −2 d −1 from Quebec palsa peatlands, Matveev et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…These results draw particular attention to the potential effect of climate change on microbial activity and trace gas production. Our study is a follow-up to numerous preceding research efforts in Central Yakutia, Northern Eurasia, focusing on microbiota and climate-relevant gas production (Cherbunina et al, 2018;Kim et al, 2019;Hughes-Allen et al, 2021). This region is underlain by thick ice-rich horizon, known as Ice Complex, a series of fine-grained Pleistocene deposits of disputed origin (Solovev, 1959;Péwé and Journaux, 1983;Ivanov, 1984;Sukhodrovsky, 2002;Vasil'chuk et al, 2004;Schirrmeister et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…For example, Zabelina et al (2021) show that CO 2 emissions from Bolshezemelskaya (northeastern European) tundra lakes are more strongly determined by lake area than any other parameter, with emissions increasing by over an order of magnitude from large to small lakes. Hughes-Allen et al (2021) show that greenhouse gas emissions from thermokarst-origin lakes in Central Yakutia (Russia) are inextricably linked to lake age, with recent thermokarst lakes acting as strong CO 2 sources throughout all seasons, whereas hydrologically closed alas lakes (formed via thermokarst processes during the early Holocene warm interval) act as CO 2 sinks during spring and fall, and much more modest CO 2 sources in winter. This finding is similar to earlier work by Anthony et al (2014), who report that Yedoma thermokarst lakes shift from being CO 2 sources, to CO 2 sinks, as they age over millennia.…”
Section: Changing Hydrology Of Lakes and Impacts On Biogeochemistrymentioning
confidence: 99%
“…While one clear conclusion from the myriad papers in this special issue is the need to continue—and even redouble—our efforts to understand the ecological and biogeochemical functioning of this rapidly changing region, broad patterns across the diverse special issue contributions highlight a number of avenues for future focus. In freshwater systems, for example, multiple studies indicated the possibility for predicting biogeochemical and ecological responses based on landscape (rivers and lakes) and morphological (lakes) characteristics (e.g., Hughes‐Allen et al 2021; Richardson et al 2021; Shogren et al 2021; Préskienis et al 2021). Although these drivers may vary across ecoregions, they are critical to consider for upscaling efforts, and should be further investigated—in particular the potential for integrating two or more fundamental variables into remote sensing products.…”
Section: Feedbacks and Scalingmentioning
confidence: 99%